1995
DOI: 10.1149/1.2048496
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Epitaxial Silicon Thin‐Film Growth on a Rotating Substrate in a Horizontal Single‐Wafer Reactor

Abstract: The effect of substrate rotation on transport of reactive gases and epitaxial growth rate is investigated for a horizontal single-wafer reactor using a model and experiments. The governing equations for gas velocity, temperature, and chemical species transport are solved for the SiHCI3-H2 system for Si thin-film preparation. The rotating substrate causes a circulating gas flow region above itself in which an asymmetric and nonuniform SiHCI3 distribution is formed by thermal diffusion and species consumption du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 2 publications
0
32
0
Order By: Relevance
“…In the previous study [12], a slow substrate rotation had been shown to have an averaging effect on the epitaxial growth rate along the concentric circle of the rotating silicon substrate, typically in a horizontal reactor. However, such a slow rotation does not influence the entire transport phenomena in the reactor, such as the gas flow, heat and species transport.…”
Section: Gas Concentration and Epitaxial Growth Ratementioning
confidence: 99%
“…In the previous study [12], a slow substrate rotation had been shown to have an averaging effect on the epitaxial growth rate along the concentric circle of the rotating silicon substrate, typically in a horizontal reactor. However, such a slow rotation does not influence the entire transport phenomena in the reactor, such as the gas flow, heat and species transport.…”
Section: Gas Concentration and Epitaxial Growth Ratementioning
confidence: 99%
“…5, as the classical ways. 15 Because the slow wafer rotation at 4 rpm has the effect of averaging the film growth rate along the concentric circle, 12 the epitaxial film thickness was expected to become flat over the wafer. Silicon carbide has a high thermal conductivity 16 which can help decrease the temperature difference over the wafer.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, wafer rotation is a popular and effective method in many CVD reactors for averaging the temperature distribution and the film growth rate over the concentric circle of the wafer. 12 In this study for achieving a quick thermal process, the heating behavior was evaluated using two types of reflectors, i.e., the Type-I reflector made of thick mirror plates used in our previous studies [6][7][8] and the Type-II reflector made of thin plates developed in this study. Additionally, the wafer rotation and the silicon carbide susceptor were shown to be effective for preparing a uniformly thick silicon epitaxial film.…”
mentioning
confidence: 99%
“…4), such as horizontal rectangular duct reactors [14,[76][77][78][79][80][81][82], vertical impinging jet and rotating disk reactors [22,[83][84][85][86][87][88], pancake reactors [89,90], barrel reactors [91][92][93], planetary reactors [94][95][96], hot-wall multi-wafer LPCVD reactors [74,[97][98][99]. Many studies were devoted to low pressure single wafer reactors of the stagnation flow type [21,28,[100][101][102]. Studied CVD processes included atmospheric pressure CVD of epitaxial Si, SiC and CdTe, MOVPE of GaAs, GaN and InP, and low pressure deposition of doped and un-doped poly-Si, tungsten, silicon-dioxide and silicon-nitride.…”
Section: Cvd Simulation Models: a Literature Reviewmentioning
confidence: 99%